A Novel Realization of Three-D Rounding Photography System - HUANG Jun-sheng; HOU Zhen-jie; ZHANG Jian-hua (Institute of Advanced Engineering and Science, 2013)
Three-D rounding photography system is an application of Desktop Virtual Reality. It takes the pictures around the objects with the computer, and then deasl with them for the 360 degree display in the local computer or a web page. The Three-D visual sense and image real-time amplification of this system are the key technical problems. This paper researches on this system and proposes a new solution based on the Silverlight technology togher withan improved triangle internal interpolation method based on the barycentric coordinates properties for the image real-time amplification.The experimental results show that the solution meets the visual sense and interaction Requirements of the Three-D Rounding Photography system. And the improved algorithm reduces the operation time efficiently, thus it has some practical value. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2205